2018
DOI: 10.1590/1806-90882018000600005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fire on Flowering and Fruiting of Anacardium Humile (Anacardiaceae) in Cerrado Stricto Sensu

Abstract: Knowledge about the effects of fire on sexual reproduction of Cerrado woody species is fundamental for elaborating public policies and management plans for its conservation. The present study evaluated the effect of a controlled burning on flowering and fruiting of Anacardium humile in an Cerrado stricto sensu environment, in Cavalcante, GO. An area with no fire records for five years was submitted to controlled burning in May 2016, used as the experimental area and its adjacent areas protected from fire as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Quantifying PFF at the community scale is less conducted in savannas than in other regions, and most observations have been made for single, mainly shrub, species (Franceschinelli & Bawa, 2005; Conceição & Orr, 2012; de Sousa & da Cunha, 2018; Dodonov et al, 2018; Shearman et al, 2019, but see Massi et al, 2017; Pilon et al, 2018). In Lamont and Downes’ (2011) review of PFF in Australasia and South Africa, the vast majority of species identified as having this strategy (>70%) were from mediterranean climate regions, whereas only ~14% were from savanna.…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying PFF at the community scale is less conducted in savannas than in other regions, and most observations have been made for single, mainly shrub, species (Franceschinelli & Bawa, 2005; Conceição & Orr, 2012; de Sousa & da Cunha, 2018; Dodonov et al, 2018; Shearman et al, 2019, but see Massi et al, 2017; Pilon et al, 2018). In Lamont and Downes’ (2011) review of PFF in Australasia and South Africa, the vast majority of species identified as having this strategy (>70%) were from mediterranean climate regions, whereas only ~14% were from savanna.…”
Section: Discussionmentioning
confidence: 99%
“…Anacardium humile has a low potential for sexual reproduction (Carvalho et al 2005). In 2016, the fruit production by the studied population was low (Sousa & Cunha 2018b). Therefore, we believe that natural regeneration had a low contribution to the abundance observed in the LF area.…”
Section: Discussionmentioning
confidence: 87%
“…The presence of xylopodium provides protection and resistance to fire and drought (Agostini-Costa et al 2016), which makes it frequent in burned environments (Loiola et al 2010). In the territory of the Kalunga, the flowering occurs between May and September, with fruiting occurring from July to September (Sousa & Cunha 2018b). The high ratio of 4:1 between male and hermaphrodite flowers (Almeida et al 1998), the inability of some hermaphrodite flowers to turn into fruits, the tendency of stamen pollen grains to remain attached to the anther after dehiscence, and the existence of only one fertile stamen in the staminate flowers are mentioned as reasons for its poor pollination (Ferrão 1995).…”
Section: Studied Speciementioning
confidence: 99%
See 1 more Smart Citation
“…This continuous effect leads to changes in the seed bank and seed dispersal (Cirne & Miranda 2008) as well as plant species' recruitment and mortality rates (Medeiros & Miranda 2005;Bouchartdet et al 2015). Therefore, the marked effects of anthropogenically altered burning frequencies on different plant species populations can alter the community as a whole (Whelan 1995).…”
Section: Introductionmentioning
confidence: 99%